QUALITY OF SERVICES PROVIDED TO THE PATIENTS IN GOVERNMENT GENERAL HOSPITAL, SRIKAKULAM–A CROSS-SECTIONAL STUDY - RAO, TATAVARTI SRINIVASA; SUBBALAKSHMI, TELIDEVARA DURGA POORNA; KANTA, HELENA (International Journal of Current Pharmaceutical Research, 2024)
Objective: To assess the quality of services provided in Outpatient department (OPD), to the Inpatients (IP) and quality of Supportive services. Methods: This is a hospital-based cross-sectional study. Feedback was taken from the 150 patients after taking permission from the concerned authorities of the hospital, after taking Institutional ethical committee approval and after written consent from the patients. Feedback is taken from the patients attending 5 departments, namely (Medicine, Surgery, Gynaecology and Obstetrics, Orthopaedics and Paediatrics. Opinion from30 patients from each department covering 15 Outpatients and 15 inpatients were taken. Results: Most of the patients of Out Patient Department (OPD) and Inpatients (IP) have expressed satisfaction regarding the services they are receiving/received from the hospital. Conclusion: Utilizing the available hospital resources judiciously with wholehearted commitment from the available manpower with time to time needed budgetary support from the Government can improve the quality of services in the Government hospitals at par with the corporate hospitals.